2001
DOI: 10.1203/00006450-200101000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Lung Volume Recruitment in Lambs during High-Frequency Oscillatory Ventilation Using Respiratory Inductive Plethysmography

Abstract: Monitoring lung volume is important in the treatment of acute hypoxemic respiratory failure. However, there are no tools available for lung volume measurement to guide ventilator management during high-frequency oscillatory ventilation (HFOV) and during dynamic changes in conventional ventilation (CV). We studied the performance of a new respiratory inductive plethysmograph (RIP) with modified software. We measured Delta changes in lung volume above end-expiratory volume (V(RIP)) during HFOV and studied whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Our study suggested that oxygenation requires significant heterogeneous derecruitment before appreciable change was observed. A lag in the oxygen response to volume loss from the previously recruited lung has been described in newly born term lambs (32) and pediatric lung disease piglet models receiving HFOV (24). In contrast, changes of X RS over time at a given P AW were very sensitive even to partial (i.e., dorsal) V L recruitment and derecruitment.…”
Section: Optimizing Hfov By Lung Mechanicsmentioning
confidence: 98%
“…Our study suggested that oxygenation requires significant heterogeneous derecruitment before appreciable change was observed. A lag in the oxygen response to volume loss from the previously recruited lung has been described in newly born term lambs (32) and pediatric lung disease piglet models receiving HFOV (24). In contrast, changes of X RS over time at a given P AW were very sensitive even to partial (i.e., dorsal) V L recruitment and derecruitment.…”
Section: Optimizing Hfov By Lung Mechanicsmentioning
confidence: 98%
“…Titration of positive end-expiratory pressure (PEEP) after maximal lung expansion allows tidal ventilation to be applied near the deflation limb of the pressure-volume (P-V) envelope [3], and is associated with best compliance and gas exchange [4,5], less repetitive recruitment and derecruitment of lung units [6], and reduction in ventilatorinduced lung injury [7]. Benefits have also been noted in animal models equivalent in size to term human newborns [3,8]. Clinical trials of open lung ventilation have suggested a benefit of this strategy in adults with acute lung injury [9]; similar trials have yet to be conducted in neonatal or paediatric subjects.…”
Section: Introductionmentioning
confidence: 99%
“…CXRs are also not a reliable method of quantifying subtle changes in intra-thoracic volume during mechanical ventilation [33]. We conducted a pragmatic study and used RIP, which is the only non-invasive, commercially available bedside tool that can be calibrated with good correlation to a known volume [34] to determine changes in thoracic volume. Although RIP detected as little as 10 ml instillation of air, it cannot differentiate the location or cause of a volume change.…”
Section: Left Ventral Right Ventralmentioning
confidence: 99%